2022
DOI: 10.15625/2525-2518/16160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tri(methoxysilyl)propyl methacrylate silane modified nanosilica on some properties of acrylic coating

Abstract: Acrylic emulsion resin is one of popular matrixes for both outside and inside coatings. It has low cost, high UV and weather resistance, good aesthetics and environmentally friendly. The introduction of inorganic additives in nanosize such as SiO2, TiO2, etc. into acrylic emulsion resin could improve the mechanical and thermal properties of the polymer matrix. The surface modification of nanoparticles can enhance the dispersibility of the nanoparticles in the polymer matrix. This paper presents the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been established that surface modification of TiO 2 with silica [ 17 , 18 ] or alumina (Al 2 O 3 ) [ 19 ] can suppress the photocatalytic property of TiO 2 . The surface modification of TiO 2 nanoparticles with silane coupling agents [ 12 , 20 , 21 , 22 , 23 , 24 ] and titanate coupling agents [ 25 ] was shown to improve the dispersibility of TiO 2 nanoparticles in an acrylic emulsion coating. Zeljko et al [ 26 ] investigated the effect of surface modification of TiO 2 on the properties of polyacrylate coatings for UV protection, comparing four different modifiers: nonionic emulsifier TX-100, the cationic initiator AIBA, the silane AMPTS, and the trisilanol POSS.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that surface modification of TiO 2 with silica [ 17 , 18 ] or alumina (Al 2 O 3 ) [ 19 ] can suppress the photocatalytic property of TiO 2 . The surface modification of TiO 2 nanoparticles with silane coupling agents [ 12 , 20 , 21 , 22 , 23 , 24 ] and titanate coupling agents [ 25 ] was shown to improve the dispersibility of TiO 2 nanoparticles in an acrylic emulsion coating. Zeljko et al [ 26 ] investigated the effect of surface modification of TiO 2 on the properties of polyacrylate coatings for UV protection, comparing four different modifiers: nonionic emulsifier TX-100, the cationic initiator AIBA, the silane AMPTS, and the trisilanol POSS.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanocoatings based on polymer matrices and inorganic nanoparticles have garnered attention from scientists and producers due to their exceptional advantages, including high transparency, reflective index, hardness, elastic modulus, tensile strength, and thermal stability. Incorporating nano-additives such as zinc oxide [1], titanium oxide [2], graphene oxide [3], zirconium oxide [4,5], silica [6], etc., can significantly enhance the properties of coatings due to their high specific surface area [7]. Among these nanoscale additives, zirconium oxide (ZrO 2 ) nanoparticles exhibit excellent physical, chemical, and mechanical properties [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Water-borne acrylic resins possess excellent properties, such as high UV resistance, good weather stability, color stability, environmental friendliness, and low cost [2,6]. In our previous report, we found that ZrO 2 nanoparticles modified with 3-(trimethoxysilyl)propyl methacrylate silane positively influenced the abrasion resistance of acrylic emulsion coating [16].…”
Section: Introductionmentioning
confidence: 99%